(untitled) (Jurnal Pembangunan Sosial, 2024)
The study investigates the causes of drug and substance abuse and proffers workable solutions to overcome the challenge within the private high school environment in Zimbabwe. The researchers used a qualitative research design and data collection method in the form of semi-structured interviews. The participants of this study involved five private high school learners, three private high school teachers and two headmasters from Waterfalls, Harare, Zimbabwe. Data was thematically analyzed. The study established that private high school administrations are neglecting the fundamental pillars of education, thereby compromising the standard of moral fiber in learners. Nonprocedural enrollment policies, lack of weekend and holiday rest and no sporting activities were established as the key causal factors of drug and substance abuse among learners in private high schools. The study concludes that the unconducive learning environment in private high schools in Zimbabwe is fertile ground for learners to succumb to drug and substance abuse usage. Whereas on the contrary, learners should have time to relax, play sports, and engage in creative activities. Therefore, this study recommends the enforcement of standardized healthy living principles of practice in private high schools in Zimbabwe.